Age‐dependent performance of BRAF mutation testing in Lynch syndrome diagnostics. Issue 10 (14th September 2020) - Bläker, Hendrik; Haupt, Saskia; Morak, Monika; Holinski‐Feder, Elke; Arnold, Alexander; Horst, David; Sieber‐Frank, Julia; Seidler, Florian; von Winterfeld, Moritz; Alwers, Elizabeth; Chang‐Claude, Jenny; Brenner, Hermann; et al.
Abstract: BRAF V600E mutations have been reported as a marker of sporadic microsatellite instability (MSI) colorectal cancer (CRC). Current international diagnostic guidelines recommend BRAF mutation testing in MSI CRC patients to predict low risk of Lynch syndrome (LS). We evaluated the age‐specific performance of BRAF testing in LS diagnostics. We systematically compared the prevalence of BRAF mutations in LS‐associated CRCs and unselected MSI CRCs in different age groups as available from published studies, databases and population‐based patient cohorts. Sensitivity/specificity analysis of BRAF testing for exclusion of LS and cost calculations were performed. Among 969 MSI CRCs from LS carriers in the literature and German HNPCC Consortium, 15 (1.6%) harbored BRAF mutations. Six of seven LS patients with BRAF ‐mutant CRC and reported age were <50 years. Among 339 of 756 (44.8%) of BRAF mutations detected in unselected MSI CRC, only 2 of 339 (0.6%) BRAF mutations were detected in patients <50 years. The inclusion of BRAF testing led to high risk of missing LS patients and increased costs at age <50 years. BRAF testing in patients <50 years carries a high risk of missing a hereditary cancer predisposition and is cost‐inefficient. We suggest direct referral of MSI CRC patients <50 years to genetic counseling without BRAF testing. Abstract : What's new? Lynch syndrome (LS) is the most common hereditary colorectal cancer. While these cancers usually show microsatellite instability (MSI), most MSI tumors are sporadic. Here, the authors evaluated the usefulness of testing for BRAF mutations as a way to distinguish LS cancers from sporadic cases. They found that the frequency of tumors carrying BRAF mutations in LS patients under age 50 is very similar to the frequency of those mutations in MSI cancers from that age group, suggesting that there's substantial overlap between the two groups. Thus, BRAF mutation status should not be used to exclude LS in patients under 50.